Inhibition of KCa2 Channels Decreased the Risk of Ventricular Arrhythmia in the Guinea Pig Heart During Induced Hypokalemia - Diness, Jonas Goldin; Abildgaard, Lea; Bomholtz, Sofia Hammami; Skarsfeldt, Mark Alexander; Edvardsson, Nils; Sørensen, Ulrik S.; Grunnet, Morten; Bentzen, Bo Hjorth (Frontiers in Pharmacology, 2020)
Background Hypokalemia reduces the cardiac repolarization reserve. This prolongs the QT-interval and increases the risk of ventricular arrhythmia; a risk that is exacerbated by administration of classical class 3 anti-arrhythmic agents. Small conductance Ca2+-activated K+-channels (KCa2) are a promising new atrial selective target for treatment of atrial fibrillation. Under physiological conditions KCa2 plays a minor role in ventricular repolarization. However, this might change under hypokalemia because of concomitant increases in ventricular intracellur Ca2+. Purpose To study the effects of pharmacological KCa2 channel inhibition by the compounds AP14145, ICA or AP30663 under hypokalemic conditions as compared to dofetilide and time matched controls (TMC). Methods The current at +10 mV was compared in HEK293 cells stably expressing KCa2.3 perfused first with normo- and then hypokalemic solutions (4 mM K+ and 2.5 mM K+, respectively). Guinea pig hearts were isolated and perfused with normokalemic (4 mM K+) Krebs-Henseleit solution, followed by perfusion with drug or vehicle control. The perfusion was then changed to hypokalemic solution (2.5 mM K+) in presence of drug. 30 animals were randomly assigned to 5 groups: ICA, AP14145, AP30663, dofetilide or TMC. QT-interval, VERP, arrhythmia score and VF incidence were recorded. Results Hypokalemia slightly increased KCa2.3 current compared to normokalemia. Application of KCa2 channel inhibitors and dofetilide prolonged the QT interval corrected for heart rate. During hypokalemia 4/6 hearts in the TMC group developed VF (2 spontaneously, 2 by S1S2 stimulation) whereas 5/6 hearts developed VF in the dofetilide group (2 spontaneously, 3 by S1S2 stimulation). In comparison, 0/6, 1/6 and 1/6 hearts developed VF when treated with the KCa2 channel inhibitors AP30663, ICA or AP14145, respectively. Conclusion Hypokalemia was associated with an increased incidence of VF, an effect that was exaggerated by dofetilide. In comparison, the structurally and functionally different KCa2 channel inhibitors, ICA, AP14145 and AP30663 protected the heart from hypokalemia induced VF. These results support that KCa2 inhibition may be associated with a better safety and tolerability profile than dofetilide.